2022
DOI: 10.1097/gox.0000000000004375
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media and Its Influence on Undergoing Rhinoplasty

Abstract: Introduction: Rhinoplasty is one of the most frequently performed procedures, and such treatments are becoming more common. Social media platforms are crucial in the promotion of cosmetic surgery. Hence, this study aimed to assess social media use and influence on the decision to undergo rhinoplasty among Saudi patients. Methods: This cross-sectional study was conducted by distributing a self-administered, online questionnaire among Saudi patients who had previously und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…A study found [ 7 ] that 65.7% of the patients who attended Saudi Arabian plastic surgery centers were motivated by cosmetic surgery outcomes before and after photographs uploaded on aesthetic surgeons' social media accounts. The most frequently used social media platform among patients who underwent rhinoplasty surgery was Snapchat (73.7%), followed by Instagram (12.7%) [ 8 ]. So, more exposure in celebrities with improved imaging and exposure to cosmetic Surgery information and advertisements lead to negative body image in the exposed populations.…”
Section: Introductionmentioning
confidence: 99%
“…A study found [ 7 ] that 65.7% of the patients who attended Saudi Arabian plastic surgery centers were motivated by cosmetic surgery outcomes before and after photographs uploaded on aesthetic surgeons' social media accounts. The most frequently used social media platform among patients who underwent rhinoplasty surgery was Snapchat (73.7%), followed by Instagram (12.7%) [ 8 ]. So, more exposure in celebrities with improved imaging and exposure to cosmetic Surgery information and advertisements lead to negative body image in the exposed populations.…”
Section: Introductionmentioning
confidence: 99%
“…The study suggests that false advertising of rhinoplasty on social media by influencers who have undergone the procedure may contribute to the general public's lack of awareness of rhinoplasty complications [9,10]. A study conducted by Obied et al found that most participants believed that rhinoplasty is a safe procedure, which supports the hypothesis that the public is not aware of the potential complications associated with the procedure [11]. Another study by Alghamdi et al reported that nearly 74% of the participants believed that rhinoplasty is a safe surgical procedure, highlighting the impact of social media advertising on public perception [12].…”
Section: Discussionmentioning
confidence: 98%
“…From a patient perspective, trending procedures and the advertisement of before and after photographs have been known to influence those seeking cosmetic surgery. 24 , 25 Social media users often use hashtags to spread awareness on certain trends or topics, as tagging a photograph with them not only boosts engagement, but also allows other users to easily find posts related to their topic of interest.…”
Section: Discussionmentioning
confidence: 99%